Two new pyranoflavanones from the stems of Derris reticulata - Chulabhorn Mahidol (2018)
Two new flavonoids, 4′,5-dihydroxy-8-hydroxymethyl-6″,6″- dimethylpyrano[2′,3′:7,6]flavanone (1), and 2′,3′-dihydroxylupinifolin (2) were isolated from the stems of Derris reticulata. Both compounds showed cytotoxic activity in the P-388 cell line. The structures were established by spectroscopic analysis and chemical transformations. The biosynthetic origin and the mechanism of formation of the hydroxymethyl group in compound (1) are proposed.